Analysis of The Level of Farmers Welfare in The Sekaroh Jaya Community Forest Sekaroh Village Jerowaru District East Lombok Regency - Zarkasyi, Akhmad; Markum, Markum; Wulandari, Febriana Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The management of community forests plays a critical role in enhancing rural livelihoods. This study aims to analyze the income and welfare levels of farmers managing the Sekaroh Jaya Community Forest in Jerowaru District, East Lombok. A descriptive research approach was employed using both primary and secondary data collected through interviews and surveys of 65 randomly selected farmers. Data analysis included calculating net income, total costs, revenues, and comparing welfare status to World Bank poverty thresholds. The findings show that farmers earned an average net income of IDR 13,197,188/LLG/year from forest cultivation, with additional income from side jobs (IDR 1,535,000/year) and working family members (IDR 5,732,653/year), resulting in an average household income of IDR 20,464,841/year. While individual farmer welfare remains low, household-level welfare is categorized as high. These results indicate that household-level contributions significantly uplift overall farmer welfare. The study concludes that improving welfare strategies should not solely target individual income increases but also support household economic activities. These findings contribute to forest policy development and rural livelihood improvement strategies under community-based forest management programs.